ChemInform Abstract: Solvent‐Free Buchwald—Hartwig (Hetero)arylation of Anilines, Diarylamines, and Dialkylamines Mediated by Expanded‐Ring N‐Heterocyclic Carbene Palladium Complexes. Issue 34 (4th August 2016) - Topchiy, Maxim A.; Dzhevakov, Pavel B.; Rubina, Margarita S.; Morozov, Oleg S.; Asachenko, Andrey F.; Nechaev, Mikhail S.
Abstract: The title arylation of amines with aryl bromides allows the synthesis of a wide range of secondary and tertiary aryl amines in high yields.